Current Trends in Mortality Attributable to Racial or Ethnic Disparities in Post-Surgical Population in The United States: A Population-Based Study - Christian Mpody, MD, PhD, MPH, MBA; Ana F. Best, PhD; Clara N. Lee, MD, MPP; David L. Stahl, MD; Vidya T. Raman, MD, MBA; Richard D. Urman, MD, MBA; Joseph D. Tobias, MD; Olubukola O. Nafiu, MD, FRCA, MS (Annals of Surgery Open)
Background:. No study has contextualized the excess mortality attributable to racial and ethnic disparities in surgical outcomes. Further, not much effort has been made to quantify the effort needed to eliminate these disparities. Objective:. We examined the current trends in mortality attributable to racial or ethnic disparities in the US postsurgical population. We then identified the target for mortality reduction that would be necessary to eliminate these disparities by 2030. Methods:. We performed a population-based study of 1,512,974 high-risk surgical procedures among adults (18–64 years) performed across US hospitals between 2000 and 2020. Results:. Between 2000 and 2020, the risk-adjusted mortality rates declined for all groups. Nonetheless, Black patients were more likely to die following surgery (adjusted relative risk 1.42; 95% CI, 1.39–1.46) driven by higher Black mortality in the northeast (1.60; 95% CI, 1.52–1.68), as well as the West (1.53; 95% CI, 1.43–1.62). Similarly, mortality risk remained consistently higher for Hispanics compared with White patients (1.21; 95% CI, 1.19–1.24), driven by higher mortality in the West (1.26; 95% CI, 1.21–1.31). Overall, 8364 fewer deaths are required for Black patients to experience mortality on the same scale as White patients. Similar figures for Hispanic patients are 4388. To eliminate the disparity between Black and White patients by 2030, we need a 2.7% annualized reduction in the projected mortality among Black patients. For Hispanics, the annualized reduction needed is 0.8%. Conclusions:. Our data provides a framework for incorporating population and health systems measures for eliminating disparity in surgical mortality within the next decade.